Influence of calcium lactate and sodium fluoride solution mouthwashes on enamel microhardness and dentin permeability during in-office bleaching - Gomes, Laurianne; Trindade, Mário; França, Fabiana; Amaral, Flávia; Basting, Roberta Tarkany (Brazilian Dental Science, 2022)
Objective: This study evaluated the influence of calcium lactate and sodium fluoride mouthwashes on enamel microhardness and dentin permeability during in-office bleaching. Material and Methods: For the microhardness evaluation, enamel blocks were randomly submitted to different treatments associated with in-office bleaching agent using 40% hydrogen peroxide (Opalescence Boost PF 40%/ Ultradent; 3 sessions x 40-minute each) (n = 10): 1) Control: application of bleaching agent; 2) Calcium lactate: 1-minute immersion before bleaching treatment; 3) Sodium fluoride: immersion for 1 minute before bleaching treatment; 4) Calcium lactate + sodium fluoride: 1 minute immersion in calcium lactate solution, followed by 1 minute immersion in sodium fluoride before bleaching treatment. Dentin discs received the same treatment protocols (n = 10) to evaluate permeability. Knoop microhardness and dentin permeability assessments were performed twice (at baseline and 48 hours after the end of bleaching treatment). Results: The generalized linear model considering the design of repeated measures over time showed that there was no significant difference between treatments (p = 0.9577) and between assessments (p = 0.3267) regarding Knoop microhardness. Kruskal Wallis and Dunn tests showed that calcium lactate immersion before bleaching treatment provided higher dentin permeability than other groups (p = 0.0009). Conclusion: The use of sodium fluoride solution and calcium lactate in association with in-office bleaching treatment did not influence the microhardness of tooth enamel, although calcium lactate may increase dentin permeability. KEYWORDS Tooth bleaching; Dentin; Sodium fluoride; Calcium lactate; Hardness tests.